AN ANALYSIS OF FOLLOWERS’ RECEPTION OF BPJS KESEHATAN’S INSTAGRAM AS A SOURCE OF HEALTH INSURANCE INFORMATION - Amar, Muhammad; Rochmaniah, Ainur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze followers’ reception of the BPJS Kesehatan Instagram account as a medium for disseminating information on the National Health Insurance (JKN) program. Method: A descriptive qualitative approach was employed using Stuart Hall’s encoding-decoding theory, with data collected through in-depth interviews with ten active followers of the @bpjskesehatan_ri account and content observation throughout 2024. Results: The findings show that most informants occupy a dominant-hegemonic position, accepting the messages as intended, while smaller groups demonstrate negotiated or oppositional readings. Notably, 80% of participants were based in East Java, with 60% from Sidoarjo Regency, indicating that geographic context shapes message interpretation. Although reception was generally positive, criticisms emerged regarding the use of technical language and limited interactivity, suggesting the need for more accessible and engaging communication. Novelty: This study provides new insights into how geographic and linguistic factors influence audience reception of digital public communication, emphasizing the importance of localized and interactive strategies in enhancing the effectiveness of social media use by public institutions.